2023
DOI: 10.1146/annurev-devpsych-120621-043144
|View full text |Cite
|
Sign up to set email alerts
|

The Functioning of Offspring of Depressed Parents: Current Status, Unresolved Issues, and Future Directions

Abstract: Although the intergenerational transmission of risk for depression is well documented, the mechanisms and moderators involved in this transmission of risk from depressed parents to their offspring are not clear. In this review, we discuss the progress that has been made over the past two decades in studying offspring of depressed parents and describe the maladaptive characteristics of these offspring in a diverse range of domains, including clinical, cognitive, and biological functioning. Despite recent advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 144 publications
0
1
0
Order By: Relevance
“…During pregnancy and the first year postpartum, herein referred to as the 'perinatal' period, people were uniquely vulnerable to the negative effects of the pandemic, and multiple studies have identified worsening mental health among those delivering during the pandemic [2][3][4] . Mental health conditions are already the most common pregnancy-related complication, impacting up to one in five pregnant people, 5 and are associated with long and short term maternal morbidity, 6,7 as well as impaired maternal-child attachment 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy and the first year postpartum, herein referred to as the 'perinatal' period, people were uniquely vulnerable to the negative effects of the pandemic, and multiple studies have identified worsening mental health among those delivering during the pandemic [2][3][4] . Mental health conditions are already the most common pregnancy-related complication, impacting up to one in five pregnant people, 5 and are associated with long and short term maternal morbidity, 6,7 as well as impaired maternal-child attachment 8,9 .…”
Section: Introductionmentioning
confidence: 99%